Physiological and Transcriptome Analysis Revealed the Effect of ABA on Promoting Persimmon Fruit Postharvest Deastringency - Han Zhou; Jiao-Jiao Nie; Meng-Lin Ren; Yu-Duan Ding; Ya-Xiu Xu; Qing-Gang Zhu (Life)
Persimmon (Diospyros kaki Thunb.) fruit can accumulate proanthocyanidins (tannins) during development, which causes astringency and affects consumption. The hormone abscisic acid (ABA) has been reported to play a key role in fruit ripening and softening. However, the effect of ABA on postharvest persimmon fruit deastringency remains unclear. In this study, we found that 300 mg/L ABA treatment could decrease the content of soluble tannins, thus leading removal of persimmon fruit astringency. The contents of acetaldehyde and ethanol did not increase during the storage time, indicating that ABA treatment-promoted persimmon fruit deastringency was not due to the acetaldehyde interaction with soluble tannins. Furthermore, the transcriptome analysis showed that 6713 differentially expressed genes (DEGs) were identified, and the WGCNA (weighted gene co-expression network analysis) showed that one module, which comprises 575 DEGs, significantly correlated with the contents of soluble and resoluble tannins. The analysis based on the carbohydrate metabolism pathway indicated that 37 differentially expressed structural genes involved in acetaldehyde metabolism were upregulated by ABA. Real-time quantitative PCR showed that the previously reported key genes, including structural genes and transcription factors, were all upregulated by ABA treatment. The obtained results indicate that ABA treatment, promoting persimmon fruit astringency removal, may occur through gel polymerization of cell wall materials with soluble tannins.